How do you put Spore together? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
We continue the interview between CTA staff and Spore, started in Spore 101, and explain, in response to many readers' queries, how Spore is produced. It's a tight and complex process, exercising intellects and logistics. In its evolution over the...